2020
DOI: 10.1177/1941738120901670
|View full text |Cite
|
Sign up to set email alerts
|

Cannabis Use and Sport: A Systematic Review

Abstract: Context: Cannabis use has increased, in large part due to decriminalization. Despite this increase in usage, it remains unclear what proportion of athletes use cannabis and what effect it has on athletic performance and recovery. Objective: To systematically review cannabis use among athletes, including epidemiology, effect on performance and recovery, and regulations for use in sport. Data Sources: PubMed, MEDLINE, and EMBASE databases were queried from database inception through November 15, 2018. A hand sea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 57 publications
0
41
0
4
Order By: Relevance
“…The establishment of the World Anti-Doping Agency (WADA) and subsequent penalisation of athletes for cannabis use has prompted greater scrutiny of the effects of cannabis effects on athletic performance (Hilderbrand 2011). Docter et al (2020) reviewed the epidemiology of cannabis use in student and elite athletes, finding that approximately one in four had used cannabis in the past year and that athletes commonly believed that cannabis would negatively affect their performance, consistent with research findings suggesting that cannabis is nonergogenic and potentially ergolytic.…”
Section: Introductionmentioning
confidence: 81%
“…The establishment of the World Anti-Doping Agency (WADA) and subsequent penalisation of athletes for cannabis use has prompted greater scrutiny of the effects of cannabis effects on athletic performance (Hilderbrand 2011). Docter et al (2020) reviewed the epidemiology of cannabis use in student and elite athletes, finding that approximately one in four had used cannabis in the past year and that athletes commonly believed that cannabis would negatively affect their performance, consistent with research findings suggesting that cannabis is nonergogenic and potentially ergolytic.…”
Section: Introductionmentioning
confidence: 81%
“…Evidence has shown that a third of cyclists, triathletes, and runners are or have been cannabinoids users (mostly ≥ 40 years of age, male, THC + CBD consumers ≤3 times weekly, and exercise 5–7 days per week) ( Zeiger et al, 2019 ). Also, a quarter of university athletes report using cannabis-related products ( Docter et al, 2020 ). Especially in contact sports like rugby, the use rate of CBD is 28%, increasing with age, and reporting pain relief and sleep quality improvements as perceived benefits ( Kasper et al, 2020 ).…”
Section: Prevalence In the Use Of Cbd Among Athletesmentioning
confidence: 99%
“…Unlike tetrahydrocannabinol (THC), CBD does not cause psychotomimetic and psychotropic reactions ( WHO, 2017 ) for which there is no evidence of dependence or abuse, but causes mild and infrequent side effects ( Stout and Cimino, 2014 ). On the contrary, CBD use is not only extensive among athletes ( Docter et al, 2020 ), but it has been shown to have specific properties that help to treat chronic pain, spasticity, mood and sleep disorders, immunodepression, inflammation, oxidant effects, and anxiety in clinical patients ( McPartland et al, 2015 ; Whiting et al, 2015 ; Nichols and Kaplan, 2019 ; Pinto et al, 2020 ). These effects could improve and accelerate recovery caused by a prolog or intense physical, physiological, and cognitive efforts as in sports ( Higgins et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, it is now possible to do a systematic review of systematic reviews [ 3 ]. Whether it be for noncancer [ 4 ] or cancer pain [ 5 ], psychiatric disorders [ 6 ] or athletic performance [ 7 ], the conclusions across these reviews are similar—clinical trial data with cannabinoid products demonstrates mild to no benefit. Evidence-based medicine rubrics typically place systematic reviews on a pedestal as the highest form of evidence.…”
Section: Current State Of Affairsmentioning
confidence: 99%